Fe-Co-based soft magnetic material and method for manufacturing the same

JP7933626B2Active Publication Date: 2026-10-13MITSUBISHI HEAVY IND LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2022172285
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-10-27
Publication Date
2026-10-13
Estimated Expiration
2042-10-27

AI Technical Summary

Benefits of technology

【0012】 本開示によれば、従来法よりも鉄損を低減しつつ、磁化特性が改善されたFe-Co系軟質磁性材料を製造できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007933626000001
    Figure 0007933626000001
  • Figure 0007933626000002
    Figure 0007933626000002
  • Figure 0007933626000003
    Figure 0007933626000003
Patent Text Reader

Abstract

To provide an Fe-Co soft magnetic material having improved magnetization characteristics while reducing iron loss more than a conventional method, and a method for producing the same.SOLUTION: In a method for producing the Fe-Co soft magnetic material according to the present disclosure, a rolled material composed of an Fe-Co alloy containing Co: 40-60%, V: 5.0% or less, Si: 3.0% or less, Al: 3.0% or less, C: 0.1% or less by weight, and one or more kinds selected from Cr, Ni, Mn, Ti, Mo, Nb, W, and Zr as necessary in total 10% or less, and the remaining of Fe and inevitable impurities, is heated at a rate of 300°C / hr or higher to a temperature in the temperature region where the irregular phase is stable, magnetically annealed at a temperature in the temperature region where the irregular phase is stable, and then cooled at a rate of 4000°C / hr or higher.SELECTED DRAWING: Figure 8
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This disclosure relates to an Fe-Co-based soft magnetic material and a method for producing the same. [Background technology]

[0002] Laminated steel sheets are used as core materials in various types of motors. Laminated steel sheets can be thin sheets or electrical steel sheets. For high-power motors, the use of Fe-Co alloys (Permendur), which have superior magnetization properties, is being considered instead of ordinary electrical steel sheets.

[0003] In recent years, thin sheets of Fe-Co alloys are often manufactured by cold rolling in the final process. After being laminated into a predetermined shape, the Fe-Co alloy sheets are annealed (magnetic annealing) to enhance their magnetization properties before use (see Patent Document 1). [Prior art documents] [Patent Documents]

[0004] [Patent Document 1] Japanese Patent Application Publication No. 1-255645 [Overview of the project] [Problems that the invention aims to solve]

[0005] Co, a component of Fe-Co alloys, is an expensive material. Therefore, general-purpose motors primarily use electrical steel sheets, which are less expensive than Fe-Co alloys. Currently, the application of Fe-Co alloys is limited to some high-power motors, resulting in limited usage experience and room for improvement in methods such as magnetic annealing.

[0006] In conventional magnetic annealing methods, the alloy is heated to a temperature higher than the regular-disorder transformation point (a temperature in the region where the disordered phase is stable), held for 1-10 hours, and then furnace-cooled at a rate of 100-300°C / hr. Alloys magnetically annealed using this method exhibit high iron loss in the frequency range below kHz. Hysteresis loss is dominant in the iron loss in the frequency range below kHz. Hysteresis loss tends to be more dominant in iron loss as the plate thickness decreases.

[0007] High iron loss reduces motor efficiency or increases heat generation in the motor. Reduced motor efficiency leads to lower power output per unit weight. As a result, the product weight increases to achieve the same power output.

[0008] This disclosure is made in view of these circumstances and aims to provide an Fe-Co-based soft magnetic material and a method for manufacturing the same that reduces iron loss compared to conventional methods without impairing magnetization properties. [Means for solving the problem]

[0009] To solve the above problems, the method for manufacturing the Fe-Co-based soft magnetic material of this disclosure is employed as follows.

[0010] One aspect of this disclosure provides a method for producing an Fe-Co soft magnetic material, comprising magnetic annealing a rolled Fe-Co alloy, which contains, by weight %, Co: 40-60%, V: 5.0% or less, Si: 3.0% or less, Al: 3.0% or less, C: 0.1% or less, and optionally one or more selected from Cr, Ni, Mn, Ti, Mo, Nb, W, Zr in total of 10% or less, with the remainder being Fe and unavoidable impurities, at a temperature in the temperature range in which the disordered phase is stable, and then cooling at a rate of 4000°C / hr or higher.

[0011] One aspect of this disclosure is a composition in weight percent of Co: 40-60%, V: 5.0% or less, Si: 3.0% or less. A Fe-Co based soft magnetic material obtained by subjecting a rolled material of a Fe-Co based alloy, which contains Al: 3.0% or less, C: 0.1% or less, optionally further contains one or more elements selected from Cr, Ni, Mn, Ti, Mo, Nb, W and Zr in a total amount of 10% or less, with the balance being Fe and unavoidable impurities, to annealing treatment, and has a Vickers hardness of 230 HV or less Furthermore, the average value of the reciprocal of the crystal grain size in the structure is 0.13 μm -1 The following is A Fe-Co based soft magnetic material is provided. [Effects of the Invention]

[0012] According to the present disclosure, it is possible to produce a Fe-Co based soft magnetic material with improved magnetization properties while reducing iron loss compared with conventional methods. [Brief Description of the Drawings]

[0013] [Figure 1] It is a phase diagram of a Fe-Co binary system. [Figure 2] It is a schematic diagram showing the pinching of a rolled material. [Figure 3] It is a cross-sectional microstructure photograph (taken with an optical microscope) of a Fe-Co based soft magnetic material that has been subjected to magnetic annealing by a conventional method. [Figure 4] It is a cross-sectional microstructure photograph (taken with an optical microscope) of a Fe-Co based soft magnetic material that has been subjected to magnetic annealing at a heating rate faster than that of conventional methods. [Figure 5] It is a diagram showing the crystal grain size information of the Fe-Co based soft magnetic material (A) produced according to the first embodiment. [Figure 6] It is a diagram showing the theoretical formula of iron loss (W). [Figure 7] It is a diagram showing the results of a Vickers hardness test (test load: 0.1 kgf). [Figure 8] It is a diagram showing the relationship between the average value of the reciprocal of the crystal grain size (μm⁻¹) of the Fe-Co based soft magnetic material and the iron loss (W / kg). [Figure 9] It is a diagram showing the relationship between the magnetizing force and the magnetic flux density of the Fe-Co based soft magnetic material (A) produced according to the first embodiment. [Modes for Carrying Out the Invention]

[0014] An embodiment of the Fe-Co-based soft magnetic material and its manufacturing method according to this disclosure will be described below with reference to the drawings. The Fe-Co-based soft magnetic material according to this disclosure is preferably applied to motors.

[0015] [First Embodiment] In this embodiment, a rolled material made of an Fe-Co alloy is magnetically annealed at a temperature in the temperature range where the disordered phase is stable, and then cooled at a rate of 4000°C / hr or higher to produce an Fe-Co soft magnetic material.

[0016] (Rolled material) Fe-Co alloys (Permendur) contain, by weight, Co: 40-60%, V: 5.0% or less, Si: 3.0% or less, Al: 3.0% or less, and C: 0.1% or less. Fe-Co alloys may also contain, if necessary, one or more elements selected from Cr, Ni, Mn, Ti, Mo, Nb, W, and Zr in a total amount of 10% or less (by weight). The remainder consists of Fe and unavoidable impurities.

[0017] Of the above components, V, Si, Al, and C are essential components, so cases where they are 0% are not included. "Unavoidable" means that, during the manufacturing process from the melting of the material to plastic deformation, the alloy components are included in the material, even though they are not intended additive elements, because their inclusion is unavoidable.

[0018] The rolled material is a strip material formed to a predetermined thickness by melting the raw Fe-Co alloy and hot rolling and / or cold rolling. The composition of the strip material is substantially the same as the raw Fe-Co alloy. The predetermined thickness may be 0.35 mm or less. The rolled material can be subjected to subsequent magnetic annealing, either individually or in stacks of multiple sheets.

[0019] (Magnetic annealing) The rolled material is placed in a heat treatment furnace, heated to a temperature range where the disordered phase is stable, and then held at that temperature for a predetermined time to undergo magnetic annealing.

[0020] During magnetic annealing, the heat treatment furnace may be in an atmosphere of air, nitrogen, inert gas, hydrogen, or a vacuum. A hydrogen environment is preferred during magnetic annealing. The heating rate is 300°C / hr or higher. The holding time is between 1 hour and 10 hours.

[0021] Figure 1 shows an example of the phase diagram of an Fe-Co binary system (Source: ASM Alloy Phase Diagram Database Volume 2). According to Figure 1, when the Co content is 49% by weight, the ordered phase (α in Figure 1) is formed. 1 The phase transformation temperature (order-disorder transformation point) from the disordered phase (αFe in Figure 1) is 730°C. According to Figure 1, when the Co content is 54% by weight, the phase transformation temperature from the disordered phase to the γFe phase (αCo,γFE in Figure 1) is 985°C.

[0022] The phase transformation temperature in the Fe-Co-V ternary system with added V is 20-30°C lower than that of the Fe-Co binary system. Based on this, the temperature in the disordered phase region (the temperature range in which the disordered phase is stable) is around 710-700°C when the Co content is 54%, and around 965-955°C when the Co content is 49%.

[0023] (cooling) After magnetic annealing, the rolled material is cooled at a rate of 4000°C / hr or higher. This cooling rate can be achieved by removing the rolled material from the heat treatment furnace after magnetic annealing and cooling it by air or water, or by blowing it with nitrogen, hydrogen, or an inert gas.

[0024] In this embodiment, the rolled material may be sandwiched between clamping members from both sides, the positions of the clamping members and the rolled material may be fixed, and the rolled material fixed to the clamping members may be placed inside the heat treatment furnace.

[0025] The cooling rate of the rolled material may be controlled by adjusting the thickness or number of layers of the rolled material.

[0026] Figure 2 illustrates a schematic diagram of how a rolled material is clamped. In Figure 2, the rolled material 3 is clamped between a plate-shaped first clamping member 1 and a second clamping member 2, and then a fixing member 4 is wrapped around it to fix the positions of the clamping members 1 and 2 and the rolled material 3.

[0027] The clamping member has rigidity that prevents it from deforming in response to the deformation of the rolled material due to thermal stress. For example, the clamping member may be a plate material such as stainless steel or a nickel-based alloy. Stainless steel has very low thermal conductivity and is a material with insulating properties. The clamping member is thicker than the rolled material. When stainless steel is used as the clamping member, the thickness of the clamping member may be 100 mm or less. A 100 mm thick stainless steel clamping member has sufficient weight to suppress the deformation of the rolled material, and the insulating effect can be adjusted by changing the thickness.

[0028] The cooling rate of the rolled material may be controlled by adjusting the heat capacity of the clamping members. The heat capacity can be adjusted by changing the type and / or thickness of the material of the clamping members. For example, when air-cooling in an environment with a high ambient temperature, the clamping members can be made thinner to reduce their heat capacity. This allows the rolled material to be cooled more quickly compared to when thicker clamping members are used.

[0029] The Fe-Co-based soft magnetic material produced by the manufacturing method according to this embodiment has a Vickers hardness of 230 HV or less.

[0030] The average value of the reciprocal of the grain size in the microstructure of the Fe-Co-based soft magnetic material produced by the manufacturing method according to this embodiment is 0.13 μm. -1 The following applies:

[0031] (Effects and Benefits) According to this embodiment, by raising the temperature to a temperature range in which the disordered phase is stable at a rate of 300°C / hr or higher, recrystallization in the temperature range in which the disordered phase is stable can be expected, and the crystal grains can be coarsened.

[0032] In the ordered phase, the activation energy is high. Therefore, in the temperature range where the ordered phase is stable, the driving force for crystal growth is lost due to recovery, making it difficult to control grain coarsening. In conventional magnetic annealing methods, heating is generally increased at a rate of 200°C / hr or less. When heating is increased slowly at 200°C / hr, the time spent at a temperature within the stable temperature range of the ordered phase is extended, making it easy for a fine structure to form. On the other hand, in this embodiment, grain coarsening can be achieved by increasing the heating rate compared to conventional methods.

[0033] According to this embodiment, by rapidly cooling the rolled material after magnetic annealing, the formation of ordered phases and intermetallic compound phases can be suppressed. This reduces iron loss and suppresses deterioration of magnetization properties.

[0034] Rapid cooling of rolled material can create a temperature gradient, potentially causing deformation due to thermal stress. According to this embodiment, deformation during rapid cooling can be prevented by clamping and fixing the rolled material with a clamping member.

[0035] The cooling rate of rolled material by air or water cooling also depends on the ambient temperature. By adjusting the heat capacity of the clamping members to control the cooling rate during air (or water) cooling, cooling at 4000°C / hr can be achieved more reliably.

[0036] <<Heating Rate and Grain Coarsening>> Figure 3 shows a cross-sectional image of an Fe-Co-based soft magnetic material heated at a conventional heating rate (160°C / hr). Figure 4 shows a cross-sectional image of an Fe-Co-based soft magnetic material heated at a faster heating rate (300°C / hr). In Figure 3, many fine crystal grains were observed. In contrast, the crystal grains observed in Figure 4 were larger than those in Figure 3, and there were fewer fine crystal grains. From Figures 3 and 4, it was confirmed that increasing the heating rate tended to increase the crystal grain size and decrease the number of fine particles.

[0037] <<Heating Rate and Crystal Grain Size>> Figure 5 shows the grain size information for Fe-Co-based soft magnetic material (A) manufactured at a heating rate of 300°C / hr or higher. For comparison, Figure 5 also includes the grain size information for Fe-Co-based soft magnetic material (B) manufactured by a conventional method (heating rate of 75°C / hr). All values ​​shown in Figure 5 are approximate.

[0038] The Fe-Co-based soft magnetic material (A) manufactured according to this embodiment has an average of the reciprocal of the grain size. value 0.05 (μm) -1 ), the reciprocal of the grain size center Value 0.04 (μm -1 ), average grain size value 35 μm, median grain size 28 μm, logarithmic mean of grain size value The grain size was 1.4 μm, the logarithmic median of the grain size was 1.5 μm, and the logarithmic standard deviation of the grain size was 0.330.

[0039] The Fe-Co-based soft magnetic material (B) manufactured according to the conventional method has an average of the reciprocal of the grain size. value 0.17 (μm) -1 ), the reciprocal of the grain size center Value 0.14 (μm -1 ), average grain size value 10 μm, median grain size 7 μm, logarithmic mean of grain size value The grain size was 0.87 μm, the logarithmic median of the grain size was 0.86 μm, and the logarithmic standard deviation of the grain size was 0.286.

[0040] In the Fe-Co-based soft magnetic material (A) manufactured according to this embodiment, it was confirmed that the crystal grains were coarser than those of the Fe-Co-based soft magnetic material (B) manufactured according to the conventional method.

[0041] Cooling rate and electrical resistivity Conventionally, in magnetic annealing of magnetic materials, it is common practice to slow the cooling rate to avoid thermal strain and the resulting deformation. For example, the catalogs for VACOFLIX® or VACODUR®, commercially available Fe-Co alloys from Vacuum Schmerz, recommend cooling at 100-300°C / hr. This cooling rate can be achieved by turning off the power to the heat treatment furnace after magnetic annealing and leaving the rolled material in the furnace to cool.

[0042] When the cooling rate is slow, the time the rolled material is held in the temperature range of the ordered phase during the cooling process is extended. In the temperature range of the ordered phase, the ordered phase becomes stable. Therefore, in conventional furnace cooling, an ordered structure is formed during cooling. The ordered phase has lower electrical resistivity than the disordered phase. Consequently, when a large amount of the ordered phase is formed, the electrical resistivity of the Fe-Co soft magnetic material decreases.

[0043] The electrical resistivity of Fe-Co-based soft magnetic materials obtained by magnetic annealing was measured using an electrical resistivity meter. The electrical resistivity of the Fe-Co-based soft magnetic material that was furnace-cooled at a cooling rate of 180°C / hr was 42.8 μΩcm. The electrical resistivity of the Fe-Co-based soft magnetic material that was air-cooled at a cooling rate of 4000°C / hr was 43.6 μΩcm. From these results, it was confirmed that by rapidly cooling (air-cooling) after magnetic annealing, it is possible to obtain Fe-Co-based soft magnetic materials with higher electrical resistivity than conventional (furnace-cooled) materials.

[0044] Figure 6 shows the theoretical formula for iron loss (W). In the theoretical formula (1) in Figure 6, iron loss is calculated from frequency f, saturation magnetic flux density Bm, plate thickness t, electrical resistivity ρ, and magnetic domain wall velocity V. Based on the theoretical formula for iron loss, as electrical resistivity increases, iron loss decreases.

[0045] Vickers hardness sample: Test No. 1: Fe-Co-based soft magnetic material manufactured according to this embodiment (Holding temperature 850℃, holding time: 4hr, cooling rate 4000℃ / hr) Test No. 2: Changed the cooling rate of Test No. 1 to 100°C / hr. Test No. 3: Changed the holding temperature to 600°C and the holding time to 4 hours compared to Test No. 1. Test No. 4: Rolled material after cold rolling (without magnetic annealing)

[0046] Measurement method (in accordance with JIS Z 2244-1): A square pyramidal diamond indenter was pressed into the sample surface, and after releasing the test load F (0.1 kgf), the diagonal length of the indentation remaining on the surface was measured, and the hardness was calculated.

[0047] result: Figure 7 shows the results. The hardness (HV0.1) of Test Nos. 1-4 was 228, 248, 507, and 427, respectively. The hardness of the samples magnetically annealed at 850°C (Test Nos. 1 and 2) was lower than that of the sample that was not magnetically annealed (Test No. 4). From these results, it was confirmed that magnetic annealing at a temperature in the temperature range where the disordered phase is stable (850°C) reduces the hardness of the sample compared to its initial state.

[0048] The sample held at 600°C (Test No. 3) showed higher hardness than the sample that was not magnetically annealed (Test No. 4). The intermetallic compound phase is harder than the disordered phase. In the sample of Test No. 3, it is thought that the intermetallic compound phase was formed and the hardness increased because it was held at a temperature lower than the temperature range in which the disordered phase is stable (600°C).

[0049] The sample from Test No. 2 had higher hardness than the sample from Test No. 1. The cooling rate of the sample from Test No. 2 was slower than that of the sample from Test No. 1. In Test No. 2, the slower cooling rate is thought to have led to atomic diffusion during the cooling process, forming an intermetallic compound phase. In the sample from Test No. 1, rapid cooling after magnetic annealing shortened the time the sample was held in the ordered phase temperature range (the temperature range in which the ordered phase is stable), which is thought to have suppressed the formation of the intermetallic compound phase, resulting in lower hardness.

[0050] From the above, it is understood that in the composition of the Fe-Co alloy described in the present embodiment, an intermetallic compound phase is generated while being held in a region below the order-disorder transformation point (temperature region of the ordered phase). The intermetallic compound phase is slightly formed even during the cooling process. Compared with the alloy having the composition described in the present embodiment, the intermetallic compound phase has lower magnetic properties and lower electrical resistivity. Therefore, when the generation amount of the intermetallic compound phase increases, the iron loss increases.

[0051] In another test, it has been confirmed that the sample quenched after magnetic annealing as in Test No.1 can reduce the iron loss at 1 kHz by about 10-15 W / kg, compared with the sample slowly cooled as in Test No.2.

[0052] In the rolled material made of the Fe-Co alloy having the composition described in the present embodiment, phase transformation occurs during the cooling process. It is inevitable that residual stress is generated by the phase transformation and the magnetic properties (iron loss properties) are degraded. However, according to the manufacturing method of the present embodiment, by rapidly cooling the rolled material after magnetic annealing, the precipitation of the intermetallic compound phase is suppressed, so that the degradation of magnetic properties can be avoided as compared with the conventional case.

[0053] ≪Iron Loss≫ FIG. 8 shows the average value of the reciprocal of the crystal grain size (μm of the Fe-Co soft magnetic material magnetically annealed at various heating rates and cooling methods (AC / FC) -1 ) and the iron loss. In the figure, the horizontal axis represents the average value of the reciprocal of the crystal grain size (μm -1 ), and the vertical axis represents the iron loss (standardized value) at 1 kHz. The standardized value on the vertical axis is a value with 150 W / kg set as 1.

[0054] Manufacturing conditions of the sample (sheet thickness 0.15 mm) ●: Temperature rise + furnace cooling (FC) by conventional method Heating rate 180°C / hr to 270°C / hr, holding time 4 hours Cooling rate 180°C / hr ◎: Temperature rise + air cooling (AC) by conventional method Heating rate 70°C / hr to 200°C / hr, holding time 4 hours Cooling rate 4000°C / hr or more ○: Heating up using the method according to the above embodiment + AC Heating rate: 300°C / hr to 730°C, holding time: 4 hours Cooling rate 4000℃ / hr or more

[0055] In Figure 8, the average value of the reciprocal of the crystal grain size of the samples (●) heated and cooled using the conventional method is 0.13 (μm). -1 It was larger than ). The average value of the reciprocal of the crystal grain size of the sample (〇) heated and cooled by the method according to the above embodiment was 0.13 (μm) in all cases. -1 ) or less. On the other hand, even for samples cooled by air cooling in the same manner, the average value of the reciprocal of the crystal grain size for samples (◎) where the heating rate was outside the range of the above embodiment was 0.13 (μm). -1 It was larger than ).

[0056] These results suggest that the cooling rate does not have much effect on the coarsening of the crystal grain size, and that the heating rate is the key factor. The average value of the reciprocal of the crystal grain size in the microstructure was set to 0.13 μm. -1 To achieve the following, it is necessary to heat the mixture at a rate of 300°C / hr or higher and then cool it at a rate of 4000°C or higher.

[0057] According to Figure 8, the smaller the average value of the reciprocal of the grain size, the smaller the iron loss. -1 A smaller value indicates a larger crystal grain size. In other words, it was observed that larger crystal grain sizes tend to result in lower iron loss.

[0058] Average iron loss at 1 kHz for a sample (●) of a commercially available alloy that was magnetically annealed and cooled using a conventional method. value The value is 1. The iron loss at 1 kHz of the sample (◎) produced by the method according to the above embodiment, with only the cooling rate changed, was about the same as that of the sample produced by the conventional method. In contrast, the iron loss at 1 kHz of the sample (〇) that was magnetically annealed at a heating rate of 300°C / hr or more and cooled at a rate of 4000°C or more was improved by more than 10% compared to the conventional method (●).

[0059] Magnetic flux density and transmittance Figure 9 shows the relationship between the magnetization force and magnetic flux density of the Fe-Co-based soft magnetic material (A) manufactured according to this embodiment. In the figure, the horizontal axis represents the magnetization force H (A / m), and the right vertical axis represents the magnetic flux density B (T).

[0060] In Fe-Co-based soft magnetic material (A), the magnetic flux density (B) when the magnetization force is 5000 A / m 50 ) was 2.25T or higher. General electrical steel sheet B 50 Since this is approximately 1.70, it can be said that the Fe-Co-based soft magnetic material according to this embodiment has a higher electromagnetic density than electrical steel sheets.

[0061] [Second Embodiment] This embodiment differs from the first embodiment in that the heating and holding processes are carried out under separate environments. The differences from the first embodiment will be described below.

[0062] In this embodiment, first, the rolled material is heated to a predetermined temperature in a first heat treatment furnace and held at that temperature for a period of 30 minutes or less. The environment inside the first heat treatment furnace during heating is atmospheric. The predetermined temperature is the temperature in the disordered phase region. The heating rate of the rolled material in the first heat treatment furnace is 300°C / hr or higher.

[0063] Next, the rolled material, after being held at a predetermined temperature, is transferred to a second heat treatment furnace and held at that temperature for 1 to 10 hours. The second heat treatment furnace is either a hydrogen environment or a vacuum environment. Preferably, the temperature of the rolled material before and after being transferred to the second heat treatment furnace is the same, but it is not limited to this, and temperature fluctuations before and after the transfer are permissible as long as the temperature of the rolled material is within the temperature range of the disordered phase. The transfer of the rolled material to the second heat treatment furnace should be carried out quickly to minimize the decrease in the temperature of the rolled material. After being transferred to the second heat treatment furnace, the temperature of the rolled material should be maintained above the orderly-disordered phase transformation point.

[0064] According to this embodiment, by performing magnetic annealing in a hydrogen environment or a vacuum environment, oxidation reactions on the surface of the rolled material can be suppressed. While existing heat treatment furnaces can create a hydrogen environment or a vacuum environment inside the furnace, it can be difficult to achieve a heating rate of 300°C / hr or higher. This embodiment is suitable when there is no heat treatment furnace that can achieve a heating rate of 300°C / hr or higher.

[0065] Heating of rolled material in an atmospheric environment can be carried out using a general-purpose first-generation heat treatment furnace. Therefore, achieving a heating rate of 300°C / hr is easy. The crystal grains can be coarsened by holding the material at a high temperature for less than 30 minutes. An oxide film forms on the surface of the rolled material held at a high temperature in an atmospheric environment, but this oxide film can be reduced and removed by holding the rolled material at a high temperature in a hydrogen environment or a vacuum environment.

[0066] <Note> The Fe-Co-based soft magnetic material described in the embodiments above, and the illegal manufacturing methods thereof, can be understood, for example, as follows.

[0067] In a method for producing an Fe-Co-based soft magnetic material according to a first aspect of this disclosure, a rolled material made of an Fe-Co alloy containing, by weight %, Co: 40-60%, V: 5.0% or less, Si: 3.0% or less, Al: 3.0% or less, C: 0.1% or less, and optionally one or more selected from Cr, Ni, Mn, Ti, Mo, Nb, W, Zr in total amount of 10% or less, with the remainder being Fe and unavoidable impurities, is heated at a rate of 300°C / hr or more to a temperature in the temperature range in which the disordered phase is stable, magnetically annealed at the temperature in the temperature range in which the disordered phase is stable, and then cooled at a rate of 4000°C / hr or more.

[0068] According to a first aspect of this disclosure, the thermal strain generated during rolling can be removed by magnetically annealing the rolled material having the above composition at a temperature in the temperature range where the disordered phase is stable.

[0069] The heating rate of 300°C / hr is faster than conventional methods. By heating faster than conventional methods, the time that the ordered phase is held at a temperature range where it is stable is shortened, and recrystallization of the disordered phase at a temperature range where it is stable can be expected, allowing for grain coarsening. In the microstructure of Fe-Co-based soft magnetic materials, grain coarsening leads to a reduction in iron loss.

[0070] According to this embodiment, the formation of ordered phases and intermetallic compound phases can be suppressed by cooling a rolled material that has been magnetically annealed at a temperature in the range where the disordered phase is stable, at a rate of 4000°C / hr or higher.

[0071] The rolled material is cooled from a temperature range where the disordered phase is stable, through a temperature range where the ordered phase is stable, and down to room temperature. The cooling rate of 4000°C / hr is faster than conventional methods. By increasing the cooling rate compared to conventional methods, the time the rolled material is held at a temperature range where the ordered phase is stable can be shortened. This suppresses the formation of the ordered phase. By suppressing the formation of the ordered phase, the generation of residual stress due to phase transformation is reduced, thus avoiding deterioration of magnetization properties. By lowering the degree of order at room temperature in Fe-Co soft magnetic materials, the decrease in electrical resistivity can be suppressed. As a result, Fe-Co soft magnetic materials with low iron loss can be obtained.

[0072] The intermetallic compound phase can be formed while the rolled material is held at a temperature below the ordered-disorder transformation point (a temperature range in which the ordered phase is stable). According to this disclosure, the formation of the intermetallic compound phase can be suppressed by rapidly cooling at the above rate to shorten the formation time. The intermetallic compound phase has lower magnetization properties compared to the alloy components. By suppressing the formation of the intermetallic compound phase, a Fe-Co-based soft magnetic material with high magnetization properties can be obtained.

[0073] In a method for manufacturing an Fe-Co-based soft magnetic material according to a second aspect of the present disclosure, in the manufacturing method described in the first aspect, the rolled material is sandwiched from both sides by a clamping member, the positions of the clamping member and the rolled material are fixed, and then the rolled material is magnetically annealed while sandwiched between the clamping members.

[0074] Generally, if the cooling rate is fast, a temperature gradient is created in the rolled material, which can cause deformation due to thermal stress. According to this embodiment, by sandwiching and fixing the rolled material with a clamping member, the clamping member acts as a physical barrier, thereby suppressing deformation of the rolled material.

[0075] In the method for manufacturing an Fe-Co-based soft magnetic material according to a third aspect of this disclosure, the cooling rate of the rolled material is controlled by adjusting the heat capacity of the clamping member in the manufacturing method described in the second aspect.

[0076] The above embodiment is suitable when the rolled material can be cooled by air cooling or water cooling at a cooling rate of 4000°C / hr or higher, but there is a possibility that a cooling rate of 4000°C / hr or higher cannot be achieved due to the influence of the surrounding environment, such as a high ambient temperature.

[0077] In the method for manufacturing a Fe-Co-based soft magnetic material according to the fourth aspect of this disclosure, in the manufacturing method described in any of the first to third aspects, in the magnetic annealing, the temperature is raised in an atmospheric environment at a rate of 300°C / hr or more to a temperature in the temperature range in which the disordered phase is stable, and then held for a time of 30 minutes or less, and thereafter the rolled material is moved to a hydrogen environment or a vacuum environment and held at a temperature in the temperature range in which the disordered phase is stable.

[0078] By performing the heating process in an atmospheric environment, it becomes unnecessary to create a hydrogen or vacuum environment inside the heat treatment furnace during the heating process. This increases the range of heat treatment furnaces that can be used for heating, and makes it easier to achieve heating rates of 300°C / hr or higher. By holding the material at a temperature range where the disordered phase is stable for 30 minutes or less, the crystal grains can be coarsened.

[0079] Although an oxide film may form on the surface of rolled material annealed in an atmospheric environment, this oxide film can be reduced and removed by placing the rolled material annealed in an atmospheric environment under a hydrogen environment or a vacuum environment and maintaining it at a temperature range in which the disordered phase is stable.

[0080] The Fe-Co-based soft magnetic material according to the fifth aspect of this disclosure contains, by weight %, Co: 40-60%, V: 5.0% or less, Si: 3.0% or less, Al: 3.0% or less, C: 0.1% or less, and optionally one or more selected from Cr, Ni, Mn, Ti, Mo, Nb, W, Zr in a total of 10% or less, with the remainder being Fe and unavoidable impurities. This rolled Fe-Co alloy is annealed and has a Vickers hardness of 230 HV or less.

[0081] When an intermetallic compound phase is formed, the hardness of Fe-Co-based soft magnetic materials increases. Fe-Co-based soft magnetic materials with a Vickers hardness of 230 HV or less are softer than Fe-Co-based soft magnetic materials manufactured by conventional methods. In other words, Fe-Co-based soft magnetic materials with a Vickers hardness of 230 HV or less have less intermetallic compound phase than conventional materials. Such Fe-Co-based soft magnetic materials have magnetization properties and electrical resistivity similar to those of Fe-Co-based alloys.

[0082] The Fe-Co-based soft magnetic material according to the sixth aspect of this disclosure is the Fe-Co-based soft magnetic material described in the fifth aspect, wherein the average value of the reciprocal of the grain size in the microstructure is 0.13 μm -1 The following applies:

[0083] The average value of the reciprocal of the grain size in the microstructure of Fe-Co-based soft magnetic materials manufactured by conventional methods is 0.15-0.20. According to the above embodiment, the crystal grains are coarser than those of conventional materials. Such Fe-Co-based soft magnetic materials have less iron loss than conventional materials. [Explanation of Symbols]

[0084] 1 (1st) Clamping Member 2 (Second) Clamping Member 3 Rolled material 4 Fixing members

Claims

1. A method for producing an Fe-Co soft magnetic material, comprising: heating a rolled Fe-Co alloy, which contains, by weight percent, 40-60% Co, 5.0% or less V, 3.0% or less Si, 3.0% or less Al, 0.1% or less C, and optionally one or more selected from Cr, Ni, Mn, Ti, Mo, Nb, W, and Zr in total amount of 10% or less, with the remainder being Fe and unavoidable impurities; heating the rolled material at a rate of 300°C / hr or higher to a temperature in the temperature range where the disordered phase is stable; magnetic annealing at the temperature in the temperature range where the disordered phase is stable; and then cooling at a rate of 4000°C / hr or higher.

2. A method for manufacturing an Fe-Co-based soft magnetic material according to claim 1, comprising sandwiching the rolled material from both sides with a clamping member, fixing the positions of the clamping member and the rolled material, and then magnetically annealing the rolled material while it is sandwiched between the clamping members.

3. A method for manufacturing an Fe-Co-based soft magnetic material according to claim 2, wherein the heat capacity of the clamping member is adjusted to control the cooling rate of the rolled material.

4. A method for producing an Fe-Co-based soft magnetic material according to claim 1, wherein in the magnetic annealing, the temperature is raised in an atmospheric environment at a rate of 300°C / hr or more to a temperature in the temperature range in which the disordered phase is stable, and then held for a time of 30 minutes or less, and thereafter the rolled material is moved to a hydrogen environment or a vacuum environment and held at a temperature in the temperature range in which the disordered phase is stable.

5. In weight percent, Co: 40-60%, V: 5.0% or less, Si: 3.0% or less. An Fe-Co-based soft magnetic material is obtained by annealing a rolled Fe-Co alloy, which contains Al: 3.0% or less, C: 0.1% or less, and optionally one or more elements selected from Cr, Ni, Mn, Ti, Mo, Nb, W, and Zr in total amount of 10% or less, with the remainder being Fe and unavoidable impurities. The Vickers hardness is 230 HV or less. A Fe-Co-based soft magnetic material in which the average value of the reciprocal of the grain size in the structure is 0.13 μm - 1 or less.

Citation Information

Patent Citations

  • Alloy with excellent room-temperature soft magnetic property and mechanical property, and preparation method thereof

    CN103114234A

  • Fe-co groupe magnetic alloy and its production

    JP1989255645A

  • Fe-co series magnetic alloy

    JP1994264195A

  • Magnetic material for iron core, method for producing the same, and iron core

    JP2011174103A

  • Strip of a cobalt iron alloy, laminated core and method of producing a strip of a cobalt iron alloy

    US20200299820A1